A purification process for hexamethyldisiloxane

Through the synergistic effect of nanofiber membrane adsorption, supergravity deacidification and anion exchange resin system, the problems of high moisture content, high chloride ion content and low purity of commercially available hexamethyldisiloxane products are solved, and efficient purification and quality improvement of the product are achieved.

CN116284097BActive Publication Date: 2025-04-22HUBEI XINGRUI SILICON MATERIAL CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211101914.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-09
Publication Date
2025-04-22
Estimated Expiration
2042-09-09

AI Technical Summary

Technical Problem

The commercially available hexamethyldisiloxane products have high moisture content, high chloride ion content and low purity, resulting in low quality.

Method used

The nanofiber membrane adsorption system and supergravity system combine with anion exchange resin system. The nanofiber membrane adsorbs solid impurities and chloride ions, and the supergravity system deacidizes and dehydrates, and the anion resin further ion adsorption, which synergistically reduces the moisture content, chloride ion content and acid value.

Benefits of technology

It significantly reduces the moisture content, chloride ion content and color of hexamethyldisiloxane, and improves the purity and quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284097B_ABST
    Figure CN116284097B_ABST
Patent Text Reader

Abstract

The invention relates to a purification process of hexamethyldisiloxane. Polyvinyl alcohol, polyacrylic acid and hydrophilic silicone oil are firstly used to prepare a nanofiber adsorption membrane. The nanofiber adsorption membrane, an ultra-gravity device and an anion exchange resin are independently or synergistically used to remove visible impurities, submicron and micron impurities, water, chloride ions and other unknown impurities in crude hexamethyldisiloxane to obtain high-quality hexamethyldisiloxane with low chroma, low water content and low chloride ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a crude hexamethyldisiloxane purification technology, belonging to the technical field of chemical equipment and engineering processes. Background Art

[0002] Hexamethyldisiloxane is an organic compound, a colorless transparent liquid, with a flash point of -2°C, a melting point of -59°C, a boiling point of 101°C, a saturated vapor pressure of 5.6 kPa (25°C) (the saturated vapor pressure of water is 3.169 kPa, 25°C), insoluble in water, soluble in most organic solvents, and mainly used as a capping agent, cleaning agent, demolding agent, organic synthesis intermediate, etc.

[0003] When hexamethyldisiloxane is used as an end-capping agent or modifier, firstly, water reacts preferentially with hydroxyl, alkoxy and other groups because it is more active than hexamethyldisiloxane, thus affecting the quality of the polymer; secondly, chloride ions affect the activity of acid-base catalysts, thereby affecting the polymerization rate of the polymerization reaction, and at the same time increasing the risk of equipment corrosion. Chinese CN101362777B, CN102617625B, CN103319519B, CN111004267A and the like are mainly purified by solid-liquid centrifugal separation and filtration, high-temperature distillation and inorganic salt dehydrating agent adsorption. In particular, Chinese patent CN103951692B drips trimethyl monochlorosilane into a reactor containing water and one or more condensation catalysts including cation exchange resin, activated clay and zeolite, and adds cation exchange resin etc. during the hydrolysis process, with the intention of promoting the condensation of trimethylsilanol into hexamethyldisiloxane. However, the kettle contains a large amount of water at this time, and strong acids such as cation exchange resins are easily lost and remain in the hydrolyzate, increasing the difficulty of chloride ion and wastewater treatment.

[0004] Hexamethyldisiloxane is currently produced mainly by the hydrolysis of trimethylchlorosilane using the public process. It has high water and chloride ion contents. The purity of commercially available products is 95.0-99.0%, with a high content of unknown impurities, a water content greater than 200 ppm, and a chloride ion content of 20-50 mg / kg. Summary of the invention

[0005] The present invention aims to invent a process for purifying crude hexamethyldisiloxane which can significantly reduce the water content, chloride ions and unknown impurities, in order to solve the shortcomings of commercially available hexamethyldisiloxane MM, such as high water content, high chloride ion content and low purity.

[0006] The present invention adopts the following technical solution:

[0007] A process for purifying crude hexamethyldisiloxane comprises the following steps:

[0008] (1) Crude hexamethyldisiloxane is injected into the nanofiber membrane adsorption system, and MM-A is obtained after adsorption by the nanofiber membrane;

[0009] (2) MM-A is preheated to 50-90℃ and then enters the ultra-gravity system. The vacuum degree in the ultra-gravity system is maintained at -90~-10kpa, and the low-molecular-weight materials are extracted and enter the low-molecular-weight receiving tank. The remaining material is MM-C;

[0010] (3) Open the feed valve of the anion exchange resin system, add MM-C into the anion exchange resin system, and obtain purified hexamethyldisiloxane after treatment with the anion exchange resin, which is named MM-D.

[0011] The crude hexamethyldisiloxane has a chromaticity greater than 50 Hazen, a purity of 95.0-99.0%, a water content greater than 200 ppm, and a chloride ion content greater than 50 mg / kg.

[0012] The nanofiber membrane is prepared by mixing polyvinyl alcohol, polyacrylic acid and hydrophilic silicone oil in a certain proportion and spinning to obtain a nanofiber membrane semi-finished product, and the nanofiber membrane semi-finished product is cross-linked at high temperature to obtain a nanofiber membrane.

[0013] The mass concentration of the polyvinyl alcohol is 5-15%, and the molecular weight of the polyvinyl alcohol is 500g / mol-8000g / mol; the solid content of the polyacrylic acid is 20-40%, and the molecular weight is 2000g / mol-30000g / mol;

[0014] The preparation process of the hydrophilic silicone oil comprises: 20-40 parts of heptamethyltrisiloxane and 60-80 parts of polyethylene glycol allyl epoxy ether are stirred evenly, 0.1-0.5 parts of 1% chloroplatinic acid hexanol solution are added, and the mixture is reacted at 60-80° C. for 2-6 hours; the molecular weight of the polyethylene glycol allyl epoxy ether is 300-1000 g / mol.

[0015] The mass ratio of the polyacrylic acid, polyvinyl alcohol and hydrophilic silicone oil is 50-60:38-48:1-3.

[0016] The high-temperature cross-linking temperature is 120°C-220°C.

[0017] The anion exchange resin comprises a styrene-based OH-type dry anion resin with a particle size of 0.5 to 1.5 mm, a pore size of ≥20 nm, and a water content of ≤0.5%.

[0018] Nanofiber membranes, a commercially available variety, are prepared by mixing, spinning and cross-linking polyacrylic acid and polyvinyl alcohol. Adding some hydrophilic silicone oil spreading agent to the original polyacrylic acid and polyvinyl alcohol raw materials can increase the wetting speed of crude hexamethyldisiloxane on the surface of nanofibers. In addition, hydrophilic silicone oil and most particle gels contain -Si-O- groups, which can enhance their adsorption of impurities.

[0019] Crude hexamethyldisiloxane generally has poor transparency and contains a large amount of visible impurities such as rust and gel. Solid impurities, micron-sized subparticles, and metal ions all tend to absorb moisture. Analysis of raw materials shows that chloride ions and acid values ​​are mostly in the original state of hydrochloric acid and are miscible with water. The nanofiber membrane has a nanometer-scale pore structure that can provide better screening and interface adsorption effects based on size effects. Therefore, nanofiber membranes are first used to adsorb solid impurities, micron-sized subparticles, metal ions, and chloride ions, and then combined with ultra-gravity for further deacidification and dehydration, and anion resins for further ion adsorption. The synergistic effect of the three greatly reduces the acid value and chloride ion content.

[0020] Through the above technical solutions, the present invention has the following technical effects:

[0021] 1. The nanofiber adsorption membrane is prepared using three hydrophilic materials, which has a very good removal effect on visible impurities, submicron and micron-sized impurities and moisture.

[0022] 2. The chromaticity, moisture content and chloride ion content in the product are greatly reduced. The anion resin exchange system and nanofiber adsorption membrane work synergistically to reduce the moisture content, chloride ion content and acid value, and improve product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a process flow chart for purifying crude hexamethyldisiloxane, wherein the present invention comprises a hexamethyldisiloxane storage tank system A1, a hexamethyldisiloxane storage tank A1A, a hexamethyldisiloxane storage tank A1B, a condenser A1A-1, a condenser A1B-2, a nanofiber membrane adsorption system F2, a nanofiber membrane adsorption storage tank F2A, a nanofiber membrane adsorption storage tank F2B, a preheater H, an overweight system G3, an insulation storage tank with a heating jacket G3-1, a vacuum pump G3-2, a low molecular receiving tank G3-3, and an anion exchange resin system Y4. DETAILED DESCRIPTION

[0024] Example 1

[0025] Preparation of hydrophilic silicone oil: 350 g of heptamethyltrisiloxane and 750 g of polyethylene glycol allyl epoxy ether with a molecular weight of 500 g / mol were stirred evenly, 2 g of 1% chloroplatinic acid hexanol solution was added, and the mixture was reacted at 75°C for 4 h to obtain a colorless transparent liquid.

[0026] Preparation of nanofiber membrane: 10 kg of deionized water is heated to 60°C, 850 g of polyvinyl alcohol powder is added with stirring, and the mixture is heated to 85°C and maintained for 10 hours. The mixture is cooled to room temperature to obtain a polyvinyl alcohol solution with a solid content of 10%, which is set aside. 55 parts of 40% solid content polyacrylic acid, 44 parts of 10% solid content polyvinyl alcohol solution and 1 part of hydrophilic silicone oil are stirred and mixed into a uniform mixed solution, which is dehydrated to a constant mass at a constant temperature. A nanofiber membrane semi-finished product is prepared using a spinning equipment, cross-linked at a high temperature of 150°C, and cooled in a drying device to obtain a nanofiber membrane.

[0027] The spinning equipment was model DXES-3 from Shanghai Dongxiang Nanotechnology Co., Ltd., China. The spinning parameters were set as follows: solution infusion rate was 1.0 mL / h, applied voltage was 30 KV, the distance from the needle to the receiving roller was 200 mm, the roller speed was set to 25 rpm, and the slide moving distance was 200 mm. The ambient temperature and relative humidity for spinning were 23 ± 2 °C and 50 ± 5%, respectively.

[0028] Raw material information: polyvinyl alcohol (PVA) powder, molecular weight 3000g / mol, alcoholysis degree 87-89%, model 1788, provided by Shanghai Aladdin Reagent Co., Ltd., China; polyacrylic acid (PAA) solution, solid content 40%, molecular weight 10000g / mol, provided by Shaoguang Keya Fine Chemical Co., Ltd., China.

[0029] Example 2

[0030] 10 kg of crude MM with a color of 60 Hazen, a purity of 98.7%, a water content of 1500 ppm, and a chloride ion content of 80 mg / kg was selected as the starting material, and the metering pump 1 pumped MM-A2 into the primary nanofiber membrane (prepared in Example 1) at a speed of 100 g / h; MM-A2 was preheated to 70°C and then entered the ultragravity system (maintained at 75-80°C in advance), and the low molecular weight material was extracted into the low molecular weight receiving tank under the vacuum degree of -82~-78 kpa in the ultragravity system, and the remaining material was MM-C2; the feed valve of the anion exchange resin system was opened, and the metering pump 2 added MM-C2 into the anion exchange resin system at a speed of 90 g / h, and purified hexamethyldisiloxane was obtained after treatment with the anion exchange resin, which was named MM-D2.

[0031] Example 3

[0032] The 55 parts of 40% solid content polyacrylic acid, 44 parts of 10% solid content polyvinyl alcohol solution and 1 part of hydrophilic silicone oil used to prepare the nanofiber membrane in Example 1 are adjusted to 60 parts of 40% solid content polyacrylic acid, 38 parts of 10% solid content polyvinyl alcohol solution and 2 parts of hydrophilic silicone oil, and the other steps are the same as Example 2.

[0033] Example 4

[0034] The 55 parts of 40% solid content polyacrylic acid, 44 parts of 10% solid content polyvinyl alcohol solution and 1 part of hydrophilic silicone oil used to prepare the nanofiber membrane in Example 1 are adjusted to 50 parts of 40% solid content polyacrylic acid, 46 parts of 10% solid content polyvinyl alcohol solution and 4 parts of hydrophilic silicone oil, and the other steps are the same as Example 2.

[0035] Comparative Example 1

[0036] The 55 parts of 40% solid content polyacrylic acid, 44 parts of 10% solid content polyvinyl alcohol solution and 1 part of hydrophilic silicone oil used to prepare the nanofiber membrane in Example 1 are adjusted to 60 parts of 40% solid content polyacrylic acid and 40 parts of 10% solid content polyvinyl alcohol solution, and the other steps are the same as Example 2.

[0037] Example 5

[0038] In the embodiment, a spinning device is used to prepare a semi-finished nanofiber membrane, and the high-temperature cross-linking at 150° C. is adjusted to 180° C. cross-linking. The other steps are the same as in Embodiment 2.

[0039] Example 6

[0040] In the embodiment, a spinning device is used to prepare a semi-finished nanofiber membrane, and the high-temperature cross-linking at 150° C. is adjusted to 220° C. cross-linking. The other steps are the same as in Embodiment 2.

[0041] Comparative Example 2

[0042] In the embodiment, a spinning device is used to prepare a semi-finished nanofiber membrane, and the high-temperature cross-linking at 150° C. is adjusted to 240° C. cross-linking. The other steps are the same as in Embodiment 2.

[0043] The test results of Examples 2 to 6, Comparative Examples 1 and 2 are shown in Table 1 below.

[0044] Table 1 Result test data of Examples 2 to 6, Comparative Example 1 and Comparative Example 2

[0045]

[0046] Example 7

[0047] Crude MM with a color of 55 Hazen, a purity of 98.3%, a water content of 950 ppm, and a chloride ion content of 60 mg / kg was selected as the starting material, and the rest was the same as in Examples 1 and 2.

[0048] Example 8

[0049] Crude MM with a color of 51 Hazen, a purity of 98.1%, a water content of 450 ppm, and a chloride ion content of 62 mg / kg was selected as the starting material, and the rest was the same as in Examples 1 and 2.

[0050] Example 9

[0051] Crude MM with a color of 45 Hazen, a purity of 99.3%, a water content of 150 ppm, and a chloride ion content of 40 mg / kg was selected as the starting material, and the rest was the same as in Examples 1 and 2.

[0052] Example 10

[0053] Crude MM with a color of 51 Hazen, a purity of 98.1%, a water content of 4500 ppm, and a chloride ion content of 62 mg / kg was selected as the starting material, and the rest was the same as in Examples 1 and 2.

[0054] The test data of the results of Examples 7 to 10 are shown in Table 2.

[0055] Table 2 Results and test data of Examples 7 to 10

[0056]

[0057] Embodiment 11

[0058] The speeds of metering pump 1 and metering pump 2 were adjusted to 50 g / h and 45 g / h respectively, and the other steps were the same as those in Example 2.

[0059] Comparative Example 3

[0060] The speeds of metering pump 1 and metering pump 2 were adjusted to 200 g / h and 180 g / h, respectively. The other steps were the same as those in Example 2.

[0061] Example 12

[0062] After metering pump 1 pumps the liquid into the primary nanofiber membrane at a rate of 260 g / h, it continues to pump the liquid into the secondary nanofiber membrane at a rate of 180 g / h. The other steps are the same as those in Example 2.

[0063] Embodiment 13

[0064] In Example 1, metering pump 1 enters the primary nanofiber membrane at 100 g / h and then continues to enter the secondary nanofiber membrane. The rest is the same as Example 2.

[0065] Comparative Example 4

[0066] The crude MM did not pass through the styrene skeleton anion exchange system, and the other steps were the same as in Example 12.

[0067] Comparative Example 5

[0068] The crude MM did not pass through the styrene skeleton anion exchange system, and the other steps were the same as in Example 13.

[0069] The test results of Examples 11 to 13 and Comparative Examples 3 to 5 are shown in Table 3.

[0070] Table 3 Test results of Examples 11 to 13 and Comparative Examples 3 to 5

[0071]

Claims

1. A purification process for hexamethyldisiloxane, characterized in that: The steps include: (1) crude hexamethyldisiloxane is injected into a nanofiber membrane adsorption system, and MM-A is obtained after adsorption by the nanofiber membrane. The nanofiber membrane is prepared by mixing polyvinyl alcohol, polyacrylic acid and hydrophilic silicone oil in a certain proportion and spinning to obtain a nanofiber membrane semi-finished product. The nanofiber membrane semi-finished product is cross-linked at high temperature to obtain a nanofiber membrane; (2) MM-A is preheated to 50-90℃ and then enters the ultra-gravity system. The vacuum degree in the ultra-gravity system is maintained at -90~-10kpa, and the low-molecular-weight materials are extracted and enter the low-molecular-weight receiving tank. The remaining material is MM-C; (3) Open the feed valve of the anion exchange resin system, add MM-C into the anion exchange resin system, and obtain purified hexamethyldisiloxane after treatment with the anion exchange resin, which is named MM-D.

2. The purification process of hexamethyldisiloxane according to claim 1, characterized in that: The crude hexamethyldisiloxane has a chromaticity greater than 50 Hazen, a purity of 95.0-99.0%, a water content greater than 200 ppm, and a chloride ion content greater than 50 mg / kg.

3. The purification process of hexamethyldisiloxane according to claim 1, characterized in that: The mass concentration of polyvinyl alcohol is 5-15%, and the molecular weight of polyvinyl alcohol is 500g / mol-8000g / mol; the solid content of polyacrylic acid is 20-40%, and the molecular weight is 2000g / mol-30000g / mol.

4. The purification process of hexamethyldisiloxane according to claim 1, characterized in that: The preparation process of the hydrophilic silicone oil comprises: 20-40 parts of heptamethyltrisiloxane and 60-80 parts of polyethylene glycol allyl epoxy ether are stirred evenly, 0.1-0.5 parts of 1% chloroplatinic acid hexanol solution are added, and the mixture is reacted at 60-80° C. for 2-6 hours; the molecular weight of the polyethylene glycol allyl epoxy ether is 300-1000 g / mol.

5. The purification process of hexamethyldisiloxane according to claim 1, characterized in that: The mass ratio of polyacrylic acid, polyvinyl alcohol and hydrophilic silicone oil is 50-60:38-48:1-3.

6. The purification process of hexamethyldisiloxane according to claim 1, characterized in that: The high temperature cross-linking temperature is 120℃-220℃.

7. The purification process of hexamethyldisiloxane according to claim 1, characterized in that: The anion exchange resin comprises a styrene-based OH-type dry anion resin with a particle size of 0.5 to 1.5 mm, a pore size of ≥20 nm, and a water content of ≤0.5%.

Citation Information

Patent Citations

  • Preparation method of hexamethyl disiloxane

    CN101362777B

  • Preparation method for high-quality hexamethyldisiloxane

    CN102617625B

  • A method for producing hexamethyldisiloxane using organosilicon azeotropes

    CN103319519B

  • A kind of preparation method of high-purity high-quality hexamethyldisiloxane

    CN103951692B

  • Preparation method of hexamethyldisiloxane

    CN111004267A